Potential sealing and repair of human FM defects after trauma with peptide amphiphiles and Cx43 antisense. (12th October 2020) - Barrett, David W.; Okesola, Babatunde O.; Costa, Eleni; Thrasivoulou, Christopher; Becker, David L.; Mata, Alvaro; Deprest, Jan A.; David, Anna L.; Chowdhury, Tina T.
Abstract: Objective: We examined whether peptide amphiphiles functionalised with adhesive, migratory or regenerative sequences could be combined with amniotic fluid (AF) to form plugs that repair fetal membrane (FM) defects after trauma and co‐culture with connexin 43 (Cx43) antisense. Methods: We assessed interactions between peptide amphiphiles and AF and examined the plugs in FM defects after trauma and co‐culture with the Cx43antisense. Results: Confocal microscopy confirmed directed self‐assembly of peptide amphiphiles with AF to form a plug within minutes, with good mechanical properties. SEM of the plug revealed a multi‐layered, nanofibrous network that sealed the FM defect after trauma. Co‐culture of the FM defect with Cx43 antisense and plug increased collagen levels but reduced GAG. Culture of the FM defect with peptide amphiphiles incorporating regenerative sequences for 5 days, increased F‐actin and nuclear cell contraction, migration and polarization of collagen fibers across the FM defect when compared to control specimens with minimal repair. Conclusions: Whilst the nanoarchitecture revealed promising conditions to seal iatrogenic FM defects, the peptide amphiphiles need to be designed to maximize repair mechanisms and promote structural compliance with high mechanical tolerance that maintains tissue remodeling with Cx43 antisense for future treatment.